2015
DOI: 10.1016/j.athoracsur.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Primary Tumors of the Heart in Children: A 10-Year Experience

Abstract: Operative resection is optimal for primary tumors of the heart in patients with obvious symptoms or hemodynamic changes. Rhabdomyomas have the potential for spontaneous regression, and nonoperative follow-up therefore is acceptable even if symptoms appear. Operative risk is greater in younger patients and in patients with cardiac valvular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…While haemangiomas are relatively common on the skin of infants, they may also occur in internal organs but are rarely seen as an isolated cardiac tumour in children. [2][3][4] A review of 200 postmortem adult cases of cardiac haemangiomas revealed 23.1% originated in the left ventricle, with the right atrium being the most common location. 1 Clinical manifestations of a primary vascular cardiac tumour vary from individuals being asymptomatic to some experiencing shortness of breath, chest pain, palpitations or exertional fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…While haemangiomas are relatively common on the skin of infants, they may also occur in internal organs but are rarely seen as an isolated cardiac tumour in children. [2][3][4] A review of 200 postmortem adult cases of cardiac haemangiomas revealed 23.1% originated in the left ventricle, with the right atrium being the most common location. 1 Clinical manifestations of a primary vascular cardiac tumour vary from individuals being asymptomatic to some experiencing shortness of breath, chest pain, palpitations or exertional fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tumors are extremely rare in both adults and children. 29 The incidence of cardiac tumors in the pediatric population depends on the age and the specific characteristics of the cohort examined (symptomatic vs asymptomatic, autopsy vs prenatal diagnosis, surgically excised vs medically managed, etc). Overall, rhabdomyomas are the most prevalent tumor, even though the majority does not evoke any symptoms and have a tendency to spontaneously regress.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, rhabdomyomas are the most prevalent tumor, even though the majority does not evoke any symptoms and have a tendency to spontaneously regress. 19,28,29 However, in surgical series, fibromas are more frequently reported. 19 In our review, the most prevalent tumor was rhabdomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Only 12 of 299 (4%) of patients had cardiac hemangiomas. Based on this review, we strongly suggest avoidance of temptation to complete surgical resection of the giant tumors, which fill the cavity of any of the cardiac chambers with infiltration into the surrounding myocardium, valves, or chordae tendinea . The reasons for this approach to primary cardiac tumors in the pediatric population are threefold: documented poor outcome of extensive damage to the surrounding structures at the time of surgery, dominance of benign tumors in children in contrast to adults and, finally, spontaneous regression, or complete disappearance of the tumor, even after partial resection of the giant tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Carney complex with frequent recurrences of the myxoma is an exception. If feasible, tissue characterization of the tumor by magnetic resonance imaging (MRI) is strongly recommended before cardiac surgery …”
Section: Discussionmentioning
confidence: 99%